2017
DOI: 10.1111/jjns.12180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurses’ personality traits and their environmental characteristics on their workplace learning and nursing competence

Abstract: Positive personality traits, such as extraversion, conscientiousness, and openness to experience could enhance workplace learning and nursing competence. Moreover, environmental characteristics that allow nurses to express their personality traits have the potential to improve their learning and competence further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
0
32
0
1
Order By: Relevance
“…This finding could help explain the fact that nurses are better than doctors at perceiving the emotions of others and generating empathy in clinical practice (André et al 2017). Many previous studies have analysed personality traits in nursing personnel and noted that a neurotic personality tendency indicates anxiety, depression, hostility, impulsivity, and other similar character traits (Chen et al 2018; Herman et al 2013; Takase et al 2018). Nurses in this study showed a low neurotic personality tendency, which is helpful for harmony among nurses, patients, and doctors and the construction of a cooperative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could help explain the fact that nurses are better than doctors at perceiving the emotions of others and generating empathy in clinical practice (André et al 2017). Many previous studies have analysed personality traits in nursing personnel and noted that a neurotic personality tendency indicates anxiety, depression, hostility, impulsivity, and other similar character traits (Chen et al 2018; Herman et al 2013; Takase et al 2018). Nurses in this study showed a low neurotic personality tendency, which is helpful for harmony among nurses, patients, and doctors and the construction of a cooperative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies had both formal and informal learning perspectives; for instance, the research conducted by Takase et al (2018) included learning from practice, others, training, feedback and reflection. In addition, six studies (Clarke, 2005; Dang and Chou, 2020; Daryoush et al , 2013; Moon and Na, 2009; Rowden and Conine, 2005; Shah et al , 2019) had formal, informal and incidental learning for the perspectives on workplace learning, whereas one study (Sadeghi, 2020) had formal, informal and non-formal learning.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 3, workplace learning has been investigated by several scholars as a mediator or moderator (Huo and Boxall, 2020; Molino et al , 2013; Nikolova et al , 2014; Reio and Wiswell, 2000; Takase et al , 2018; Tengku Ariffin et al , 2014; Van der Heijden et al , 2016). Socialization-related learning as one kind of workplace learning was a mediator that linked individual curiosity and job performance (Reio and Wiswell, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Among the internal factors, personal traits should be of particular importance. It is precisely the nurses' personalities that may condition their perseverance in mastering their own skills through shaping a positive attitude towards acquiring them [22]. Personality traits are relatively constant tendencies conditioning human behavior in various situations.…”
Section: Introductionmentioning
confidence: 99%